2018
DOI: 10.1016/j.bjorl.2017.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Association of Ugrp2 gene polymorphisms with adenoid hypertrophy in the pediatric population

Abstract: Some single nucleotide polymorphisms and their combinations in the Ugrp2 gene are associated with an increased risk of developing adenoid hypertrophy. Therefore, we tried to underline the importance of genetic factors associated with adenoid hypertrophy and its related clinical phenotypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 35 publications
0
1
0
1
Order By: Relevance
“…Интересно, что другие исследования показали, что полиморфизм rs1800896 в гене IL-10 может быть Бронхопульмонология и отоларингология связан с заболеваемостью ВЭБ и вирусом, ассоциированным с гемофагоцитарным лимфогистиоцитозом (ВЭБ-ГЛГ) у детей, а генотип АА и аллель А могут быть чувствительными факторами риска для ВЭБ-ГЛГ [50]. Кроме того, в предыдущих работах было показано, что полиморфизм гена MBL2 (SNP 49 C/T rs5030737) [23], генотипы AG + GG и AG по TLR4-D299G [51], Ugrp2 [52], генотипы 2R, 2R, IL-1Ra и T и T IL-1b [53] были связаны с повышенным риском развития ГГМ. Наши результаты позволяют предположить, что генотип GG по IL-10 rs1800896 играет роль в устойчивости к ГГМ и может предотвращать разрастание ткани глоточной миндалины до максимального размера.…”
Section: Discussionunclassified
“…Интересно, что другие исследования показали, что полиморфизм rs1800896 в гене IL-10 может быть Бронхопульмонология и отоларингология связан с заболеваемостью ВЭБ и вирусом, ассоциированным с гемофагоцитарным лимфогистиоцитозом (ВЭБ-ГЛГ) у детей, а генотип АА и аллель А могут быть чувствительными факторами риска для ВЭБ-ГЛГ [50]. Кроме того, в предыдущих работах было показано, что полиморфизм гена MBL2 (SNP 49 C/T rs5030737) [23], генотипы AG + GG и AG по TLR4-D299G [51], Ugrp2 [52], генотипы 2R, 2R, IL-1Ra и T и T IL-1b [53] были связаны с повышенным риском развития ГГМ. Наши результаты позволяют предположить, что генотип GG по IL-10 rs1800896 играет роль в устойчивости к ГГМ и может предотвращать разрастание ткани глоточной миндалины до максимального размера.…”
Section: Discussionunclassified
“…Interestingly, other studies showed that the polymorphism of rs1800896 in the IL-10 gene may be related to the incidence of EBV and Epstein-Barr virus associated with hemophagocytic lymphohistiocytosis (EBV-HLH) in children, and the AA genotype and A allele of both sites may be the susceptible risk factors for EBV-HLH [38]. Furthermore, prior works showed that the MBL2 (SNP 49 C/T rs5030737) gene polymorphism [24]; the AG + GG and AG genotypes at TLR4-D299G [39]; Ugrp2 [40]; and the 2R, 2R, Il-1Ra and T, and T IL-1b genotypes [41] were associated with an increased risk of developing adenoid hypertrophy. Our results suggested that genotype GG for IL-10 rs1800896 played a role in the resistance to adenoid hypertrophy and could prevent the expansion of the adenoid tissue to the maximum size.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, NACHT LRR and PYD domains-containing protein 3 (NLRP3)-mediated pyroptosis has been shown to be a mechanism through which IL-32 influences the progression of AH [82]. Additionally, a higher chance of developing AH has also been linked to several genetic predisposing factors [83][84][85][86]. However, in a recent study conducted in Moscow, Lomaeva et al suggested that children aged 2-11 years with the IL-10G-1082A genotype GG might be resistant to the development of AH [47].…”
Section: Aetiological Agents For Ah and Npcmentioning
confidence: 99%